A Comparative Study of the Laws of Execution of the Death Penalty Against Australian and French Citizens in Narcotics Crimes - Pradana, Alifian Maulana Nanda; Mangesti, Yovita Arie (Jurnal Hukum dan Keadilan, 2024)
This work analyzes the differences behind the protracted delay in the Serge Areski Atlaoui case which is compared to the case of the two defendants Bali Nine, namely Myuran Sukumaran and Andrew Chan, in the case of the same narcotics crime there is a very clear difference at the time of the inkracht criminal verdict. The purpose of this work is to analyze the urgency behind the moratorium on the verdict of Serge Areski Atlaoui which is different from the verdict on the two defendants Bali Nine. Through this work, two major findings were obtained, the first of which was that the moratorium on the death penalty was motivated by changes in criminal law policy through Law Number 1 of 2023 concerning the Criminal Code which provides a probation period of 10 years for defendants on death row, this was not obtained by the two defendants in the Bali Nine case because they had been executed after the PTUN decision on the lawsuit against the rejection of clemency by the President. The second finding is in the form of major implications after the reharmonization of criminal law provisions in the form of the application of the principles of legal certainty, legal justice and legal usefulness. The findings then gave a conclusion that the enforcement of criminal law against narcotics crimes has been updated by looking at the human aspect.